BARTLEBY IS DEAD: inverting common readings of melville's bartleby, the scrivener. Issue 5 (3rd September 2019) - Bojesen, Emile; Allen, Ansgar
Abstract: This paper argues against dominant philosophical interpretations of Melville's Bartleby, the Scrivener and submits it to an educational reading . It problematizes readings (such as those of Gilles Deleuze, Giorgio Agamben, and the Occupy Movement) where the character of Bartleby figures a way of being that allows us to escape or challenge our contemporary political and educational exigencies. Our contention is that an encounter with Bartleby is not politically or educationally enabling, but provokes the Lawyer, despite himself, to encounter the unedifying limits of any educational practice and discourse, as well as his necessary complicity in the context that supports them. We argue that anyone interested in education or politics would do much better to scrutinize their unavoidable affinity with the Lawyer, instead of projecting fantasies of escape on the character of Bartleby, who, in the end, only figures a giving up on life.